2020
DOI: 10.1002/eat.23384
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of internet‐based guided self‐help for binge‐eating disorder and characteristics of completers versus noncompleters

Abstract: Objective: Binge-eating disorder (BED) is characterized by recurrent episodes of binge eating, accompanied by a lack of control and feelings of shame. Online intervention is a promising, accessible treatment approach for BED. In the current study, we compared completers with noncompleters in a 10-session guided internet-based treatment program (iBED) based on cognitive behavioral therapy. Methods: Adults (N = 75) with mild to moderate BED participated in iBED with weekly written support from psychologists. Par… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
1
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 18 publications
0
19
1
1
Order By: Relevance
“…The rate of post-program completion was another important weakness. Though a severe limitation to our ability to draw firm conclusions, this is unfortunately not out of line with previous reports of dropout and/or completion of post-program assessments in internet-based programs for psychological treatments (Jensen et al, 2020;Melville et al, 2010). Linardon and Fuller-Tyszkiewicz (2020) showed in a systematic review of attrition in smartphone-based trials that studies with enrollment occurring entirely online (i.e., no face-to-face meeting with study personnel) had an average of 43.4% attrition while those with in-person enrollment showed only an 11.2% attrition.…”
Section: Limitationscontrasting
confidence: 59%
See 2 more Smart Citations
“…The rate of post-program completion was another important weakness. Though a severe limitation to our ability to draw firm conclusions, this is unfortunately not out of line with previous reports of dropout and/or completion of post-program assessments in internet-based programs for psychological treatments (Jensen et al, 2020;Melville et al, 2010). Linardon and Fuller-Tyszkiewicz (2020) showed in a systematic review of attrition in smartphone-based trials that studies with enrollment occurring entirely online (i.e., no face-to-face meeting with study personnel) had an average of 43.4% attrition while those with in-person enrollment showed only an 11.2% attrition.…”
Section: Limitationscontrasting
confidence: 59%
“…Thirty-two participants responded to the followup questionnaire for a response rate of 46%. Unfortunately, low completion and follow-up rates are relatively typical of online-based intervention trials (e.g., Jensen et al, 2020) and reports of quality outcomes data as well (e.g., Lowe et al, 2003). The present study was approved as an 'exempt' protocol by the author's Institutional Review Board (IRB-FY2020-116).…”
Section: Procedures and Participantsmentioning
confidence: 99%
See 1 more Smart Citation
“…This present paper examines the pre-treatment characteristics of participants, knowledge of which may aid clinicians in tailoring or targeting therapy efforts cognizant that people with these characteristics may be more likely to disengage with the therapy. It is also clear that more studies need to be done to determine risk factors for attrition or treatment outcome in internet-based interventions for BED [5]. Jensen et al [5] found minor differences between completers and non-completers on depression and no differences in BED-symptoms, BMI, and sociodemographic variables.…”
Section: Introductionmentioning
confidence: 99%
“…It is also clear that more studies need to be done to determine risk factors for attrition or treatment outcome in internet-based interventions for BED [5]. Jensen et al [5] found minor differences between completers and non-completers on depression and no differences in BED-symptoms, BMI, and sociodemographic variables. Participants who completed treatment showed large reductions in eating disorder pathology.…”
Section: Introductionmentioning
confidence: 99%